High-flux asymmetric alumina ceramic membrane as well as preparation method and application thereof

Alumina ceramic films are prepared by casting film method and dip coating method, combined with sintering aid and particle size control, and the problem of preparing high-throughput and special-shaped films in the prior art is solved, and high-throughput and stability are achieved, suitable for multiple type of application.

CN119215690AActive Publication Date: 2024-12-31NANJING TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411421557.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-31
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing preparation methods of asymmetric alumina ceramic films are limited by equipment, making it difficult to prepare high-throughput and special-shaped films, and problems such as film material breakage, film layer shedding and thickness unevenness are prone to occur.

Method used

The supporting layer of alumina ceramic film was prepared by casting film method, and the transition layer and separation layer were formed by dip coating. The mechanical strength was enhanced using calcined agents such as kaolin and vapor phase silica, and the particle size and thickness were controlled to achieve high throughput and stability.

Benefits of technology

Asymmetric alumina ceramic membrane with high throughput and stable performance is achieved, the preparation process is simplified, the structural integrity and separation performance of the membrane material are improved, and the adaptability is strong, suitable for oil-water separation and industrial wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215690A_ABST
    Figure CN119215690A_ABST
Patent Text Reader

Abstract

The invention relates to a high-flux asymmetric aluminum oxide ceramic membrane as well as a preparation method and application thereof. The ceramic membrane has three layers of asymmetric structures: a support layer, a transition layer and a separation layer. The alumina support layer is prepared by casting, drying and calcining support layer slurry, and the support layer slurry comprises alumina, a binder, a sintering aid and water. The aluminum oxide in the aluminum oxide supporting layer is large in particle size, the aluminum oxide in the transition layer is medium in particle size, and the aluminum oxide in the separation layer is nanoscale. The membrane is high in flux, stable in performance, small in thickness, simple in preparation process and easy to industrialize. Compared with the traditional dry pressing method, the ceramic membrane supporting layer prepared by the membrane casting method has the advantage that the flux is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic membranes, and relates to a high-flux asymmetric alumina ceramic membrane and a preparation method and application thereof. Background Art

[0002] In recent years, research in membrane separation technology has rapidly advanced. Due to its advantages, including high separation efficiency, ease of operation, pollution-free operation, and low energy consumption, this technology holds great potential for separation applications and has been applied to a wide range of systems. Unlike traditional ceramic membranes, asymmetric ceramic membranes are typically constructed from three layers of powders of varying particle sizes: a support layer composed of large particles that provide mechanical strength, a transition layer composed of medium particles that prevent particle leakage in the separation layer, and a separation layer typically composed of nanoparticles that primarily performs separation and screening functions. Due to the thin separation layer, asymmetric support ceramic membranes typically exhibit high flux and hold broad application prospects in oil-water separation and industrial wastewater treatment. However, the support layer of existing flat-plate asymmetric alumina-based ceramic membranes is often prepared using a dry-pressing method, which places high demands on equipment and can significantly affect membrane flux. Furthermore, the dry-pressing method is limited by molds, resulting in a generally fixed membrane shape and area, making it difficult to scale up and produce specialized membranes. During scale-up, conventional alumina ceramic membranes often suffer from membrane breakage, membrane shedding, and uneven thickness. Therefore, it is particularly important to explore more flexible preparation methods to improve the performance and adaptability of membranes. Summary of the Invention

[0003] In view of the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a high-flux asymmetric alumina ceramic membrane, which has high flux, stable performance, thin thickness, simple preparation process and easy industrialization.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] An alumina ceramic membrane, comprising an alumina support layer, an alumina transition layer and an alumina separation layer arranged in sequence; the alumina support layer is prepared by casting a support layer slurry, drying and calcining, the support layer slurry comprising alumina, a binder, a sintering aid and water; the sintering aid is selected from a combination of one or more of kaolin, fumed silica, titanium dioxide, zirconium oxide and yttrium oxide; the particle sizes of the alumina in the alumina support layer, the alumina in the alumina transition layer and the alumina in the alumina separation layer decrease in sequence.

[0006] In some embodiments, the sintering aid is a mixture of kaolin and fumed silica; preferably, in the mixture, the mass ratio of kaolin to fumed silica is 1:8 to 1:10.

[0007] In some embodiments, the particle size of the aluminum oxide in the aluminum oxide support layer is 4 to 20 μm, preferably 5 to 10 μm.

[0008] In some embodiments, the particle size of the aluminum oxide in the aluminum oxide transition layer is 1 to 3 μm, preferably 1 to 2 μm.

[0009] In some embodiments, the particle size of the aluminum oxide in the aluminum oxide separation layer is 200 to 800 nm, preferably 400 to 600 nm.

[0010] In some embodiments, the alumina support layer is a flat plate-shaped α-Al 2 O 3 porous ceramic support layer.

[0011] In some embodiments, the thickness of the alumina support layer is 0.5 to 2 mm.

[0012] In some embodiments, the thickness of the aluminum oxide transition layer is 5 to 25 μm.

[0013] In some embodiments, the thickness of the aluminum oxide separation layer is 15 to 25 μm.

[0014] In some embodiments, the support layer slurry includes 100 to 120 parts of aluminum oxide, 2 to 2.5 parts of a binder, 8 to 10 parts of a sintering aid, and 75 to 90 parts of water.

[0015] In some embodiments, the binder is selected from hydroxymethyl cellulose, polyvinyl alcohol, or a combination of the two.

[0016] In some embodiments, the support layer slurry further includes a dispersant, a leveling agent, a plasticizer, and a defoaming agent.

[0017] In some embodiments, the support layer slurry includes, by weight, 100 to 120 parts of alumina, 2 to 2.5 parts of dispersant, 2 to 2.5 parts of binder, 1 to 1.25 parts of leveling agent, 4 to 5 parts of plasticizer, 2 to 2.5 parts of defoaming agent, 8 to 10 parts of sintering aid and 75 to 90 parts of water.

[0018] In some embodiments, the dispersant is selected from one or more combinations of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and octadecyltrimethylammonium chloride.

[0019] In some embodiments, the leveling agent is selected from one or a combination of polydimethylsiloxane and polyacrylic acid.

[0020] In some embodiments, the plasticizer is selected from one or a combination of polyethylene glycol and dibutyl phthalate.

[0021] In some embodiments, the defoaming agent is one or a combination of tributyl phosphate and isopropyl alcohol.

[0022] The present invention also provides a method for preparing the aforementioned alumina ceramic membrane, comprising the following steps: 1) casting the support layer slurry, drying, and calcining to produce the alumina support layer; 2) impregnating the alumina support layer with a transition layer modification solution, drying, and calcining to produce an alumina transition layer; the transition layer modification solution comprising alumina and water; and 3) impregnating the alumina transition layer with a separation layer modification solution comprising alumina and water, drying, and calcining to produce the alumina ceramic membrane. The present invention utilizes a casting method to prepare the support layer of a high-throughput alumina ceramic membrane, and a dip-coating method to prepare the transition layer and separation layer of an asymmetric alumina ceramic membrane.

[0023] In some embodiments, the casting is performed in a polytetrafluoroethylene mold; preferably, the polytetrafluoroethylene mold is coated with paraffin oil as a release agent. The polytetrafluoroethylene mold can be of any size and shape, and thus the shape of the alumina ceramic membrane of the present invention is not limited.

[0024] In some embodiments, in step 1), the drying temperature is 30-40°C.

[0025] In some embodiments, in step 1), the drying time is 8 to 12 hours.

[0026] In some embodiments, in step 1), the calcination temperature is 1200-1600°C. Controlling the final sintering temperature can adjust the membrane material's properties. Alumina undergoes thermal contraction during cooling, so higher calcination temperatures result in denser particle packing, increasing mechanical strength while decreasing porosity and gas flux.

[0027] In some embodiments, in step 1), the calcination time is 1 to 3 hours.

[0028] In some embodiments, the transition layer modification liquid further includes a dispersant, a leveling agent, and a pH adjuster.

[0029] In some embodiments, the transition layer modification solution includes, by weight, 50 to 60 parts of aluminum oxide, 1 to 1.2 parts of a dispersant, 6 to 10 parts of a leveling agent, 10 to 12 parts of a pH regulator, and 500 to 600 parts of water.

[0030] In some embodiments, the pH adjuster is selected from one or both of nitric acid and hydrochloric acid. The pH adjuster can alter the charge on the particle surface. After adding the pH adjuster, the aluminum oxide groups in the modification solution simultaneously carry the same charge, enhancing charge repulsion and reducing the likelihood of agglomeration. This property reduces the overall viscosity of the modification solution and slows its sedimentation rate, allowing for long-term storage and reuse.

[0031] The types of dispersants and leveling agents in the transition layer finishing liquid can be conventional types, such as the types mentioned above in the support layer slurry.

[0032] In some embodiments, the separation layer modification liquid further comprises a dispersant, a leveling agent, and a pH adjuster.

[0033] In some embodiments, the separation layer modification solution includes, by weight, 50 to 60 parts of aluminum oxide, 1 to 1.2 parts of a dispersant, 6 to 10 parts of a leveling agent, 12 to 14 parts of a pH regulator, and 400 to 500 parts of water.

[0034] In some embodiments, the pH adjuster is selected from one or both of nitric acid and hydrochloric acid.

[0035] The types of dispersants and leveling agents in the separation layer modification liquid can be conventional types, such as the types mentioned above in the support layer slurry.

[0036] In some embodiments, the preparation method further comprises the steps of mechanically stirring and standing the support layer slurry for degassing before casting the membrane.

[0037] In some embodiments, in steps 1), 2) and 3), the calcination is performed by programmed temperature increase, and the rate of the temperature increase is 8-12° C. / min.

[0038] In some embodiments, in step 2), two alumina support layers are stacked on each other, and the gap therebetween is sealed before impregnation.

[0039] The present invention also provides use of the aforementioned alumina ceramic membrane for oil-water separation or industrial wastewater treatment.

[0040] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0041] The present invention achieves an excellent balance between membrane material flux and separation capacity by employing a three-layer asymmetric support structure. This three-layer structure is clearly visible in scanning electron microscope images. The bottom support layer is prepared using a casting method, and its thickness is significantly thinner than traditional materials. This design ensures the high flux characteristics of the membrane material. The transition layer effectively prevents leakage from the top layer, ensuring the overall stability of the membrane. The separation layer maintains an intact and smooth surface, significantly improving separation efficiency and thus enhancing the application performance of the membrane material.

[0042] The present invention innovatively adopts a casting method. By using a sintering aid, such as fumed silica, a bridge bonding is formed between the alumina particles, thereby enhancing the mechanical strength of the overall membrane material and successfully preventing undesirable phenomena such as cracking and bending of the membrane layer that are prone to occur during the process of shaping the ceramic membrane slurry into the support layer. This method not only improves the structural integrity of the membrane, but also optimizes its physical properties and ultimately improves the separation performance of the entire alumina ceramic membrane. Compared with the traditional dry pressing method, the ceramic membrane support layer prepared by the casting method of the present invention shows a significant improvement in flux.

[0043] The high-flux asymmetric alumina ceramic membrane of the present invention can be prepared by wire cutting or laser cutting to achieve heterogeneous membrane material. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the surface electron micrograph of aluminum oxide with a particle size of 400 nm;

[0045] Figure 2 This is the surface electron micrograph of 1μm aluminum oxide;

[0046] Figure 3 This is the surface electron micrograph of 10 μm aluminum oxide.

[0047] Figure 4 This is a scanning electron microscope image of a cross-section of a three-layer asymmetric alumina ceramic membrane prepared in Example 1, comprising a support layer with a 10 μm alumina powder particle size, a transition layer with a 1 μm alumina powder particle size, and a separation layer with a 400 nm alumina powder particle size;

[0048] Figure 5 The flat alumina ceramic membrane finally obtained in Example 1 and the special-shaped membrane after cutting;

[0049] Figure 6 This is the disc-shaped alumina ceramic membrane finally obtained in Comparative Example 1;

[0050] Figure 7 2 is a comparison chart of N2 flux of alumina ceramic membranes of Examples 1 and 2 and Comparative Example 1;

[0051] Figure 81 is a comparison chart of pure water flux of the alumina ceramic membranes of Examples 1 and 2 and Comparative Example 1;

[0052] Figure 9 This is the surface electron microscope image of Comparative Example 2;

[0053] Figure 10 This is the surface electron microscope image of Comparative Example 3. DETAILED DESCRIPTION

[0054] The traditional dry-pressing method for preparing the support layer suffers from insufficient membrane flux and is limited by mold constraints, resulting in a generally fixed membrane shape and area, making it difficult to scale production and prepare special-shaped membranes. The cast film method for preparing ceramic materials is quite rare and is typically used for the preparation of polymer membranes. However, the cast film method can cause cracking and bending during the preparation process. The present invention, by adding a sintering aid, bridges and bonds the alumina particles, effectively preventing cracking and increasing the mechanical strength of the ceramic membrane material.

[0055] The present invention innovatively adopts the casting method to prepare the support layer of the high-flux alumina ceramic membrane. In order to improve the permeation flux of the membrane material, alumina powder with a larger particle size is selected as the alumina of the support layer, while the thickness of the alumina ceramic membrane is greatly reduced. During the casting process of the support layer, considering the difference between the particle size of the separation layer and the support layer, a medium-sized alumina powder is first used to prepare the transition layer. The introduction of this layer effectively prevents the infiltration of alumina particles in the top separation layer. While ensuring the high flux of the membrane material, in order to improve the separation performance, alumina powder with a particle size of nanometers is used to prepare the separation layer, forming a structure with dense stacking and small pore size.

[0056] This invention provides a new approach for the scale-up of asymmetric alumina ceramic membranes. Conventional alumina ceramic membranes are often limited by the size of molds and laboratory equipment during scale-up, often leading to problems such as membrane breakage, film shedding, and uneven thickness. However, the alumina ceramic membranes produced by this invention offer high throughput, stable performance, and a streamlined production process, significantly reducing production time. These advantages offer significant advantages and are conducive to industrial application and large-scale production.

[0057] Furthermore, the present invention innovatively prepares the alumina sheet through a casting process, followed by the formation of the transition and separation layers through dipping and pulling. The resulting membrane material can be in a flat sheet form, facilitating further processing. For example, laser cutting and other techniques can be used to create a variety of heterogeneous membrane materials to meet the needs of various industrial applications.

[0058] The present invention uses a casting method to first prepare a large alumina support layer substrate, and then successfully grows a three-layer asymmetric ceramic membrane through a double dip coating method. This method significantly improves the flux of the membrane material compared to the traditional solid particle sintering method.

[0059] During the dip-coating of the alumina support layer, the present invention stacks two alumina sheets and uses raw tape to seal the gaps between the sheets, effectively preventing their backsides from contacting the alumina finishing solution. This design ensures that the transition and separation layers grow only on the front side of the support layer, avoiding growth on the backside. By precisely controlling the dip-coating process, the structural integrity and functional properties of the membrane are maintained, further enhancing the adaptability of the membrane material to various applications. This method not only simplifies the production process but also improves membrane production efficiency, giving it the potential for broader industrial applications.

[0060] The present invention will be described in further detail below by way of specific embodiments. However, it will be appreciated by those skilled in the art that the following examples are intended only to illustrate the present invention and are not to be construed as limiting the scope of the invention. Specific techniques and conditions not specified in the examples should be based on the techniques or conditions described in the literature within the art. Reagents or instruments not specified by manufacturer are all commercially available conventional products.

[0061] Example 1

[0062] This embodiment provides a method for preparing a three-layer asymmetric aluminum oxide film, and the preparation method is as follows:

[0063] Take 120g of alumina powder with a particle size of 10μm ( Figure 3 ), add 90ml of deionized water, and stir for 2 minutes. During the stirring process, 2.4g of hexadecyltrimethylammonium chloride (dispersant), 2.4g of hydroxymethyl cellulose (adhesive), 1.2g of polyacrylic acid (leveling agent), 4.8g of polyethylene glycol (plasticizer), 2.4g of isopropyl alcohol (defoamer), 8.64g of kaolin (sintering aid), and 0.96g of fumed silica were added in sequence. The casting solution was then transferred to a high-speed beater at 8000rpm and stirred at high speed for 5 hours. Ultrasonic treatment was performed for 30 minutes to eliminate foam, and the mixture was allowed to stand for 2 hours. Next, paraffin oil (a mold release agent) was evenly applied to a leveled temperature control plate set to 30°C. The casting apparatus used a polytetrafluoroethylene flat frame with a PET plastic film placed underneath. The film was dried for 12 hours. The cast film was then placed in a muffle furnace and calcined at 1400°C for 3 hours, with both the heating and cooling rates set at 10°C / min. A supporting layer (single-layer symmetrical ceramic membrane) was obtained, the thickness of which was 1 mm.

[0064] Take 56.8g of alumina powder with a particle size of 1μm, add it to 600ml of deionized water, and stir for 5min. During the stirring process, add 1.12g of dispersant hexadecyltrimethylammonium chloride, 10.46g of nitric acid and 6.67g of leveling agent polyacrylic acid in sequence, ultrasonically treat for 30min to remove foam, and prepare 1μm alumina modification liquid (transition layer modification liquid). Use a pulling instrument to pull and dip the prepared alumina support layer for 30 seconds, and dip it twice. After the dip coating is completed, dry it at room temperature for 12 hours, set the roasting temperature to 1200℃, calcine it at high temperature for 3 hours, and set the heating rate and cooling rate to 10℃ / min to prepare a double-layer asymmetric alumina ceramic membrane. The thickness of the transition layer is 10μm.

[0065] Take 51.12g of alumina powder with a particle size of 400nm ( Figure 1 ), add 500ml of deionized water and stir for 5min. During the stirring process, add 1.12g of dispersant hexadecyltrimethylammonium chloride, 12.5g of nitric acid and 6.67g of leveling agent polyacrylic acid in sequence, ultrasonically treat for 30min to remove foam, and prepare 400nm alumina modification liquid (separation layer modification liquid). The double-layer asymmetric alumina ceramic membrane prepared above is pulled and dipped for 30 seconds using a pulling instrument, and dipped twice. After the dip coating is completed, dry at room temperature for 12 hours, set the roasting temperature to 1200℃, calcine at high temperature for 3 hours, and set the heating rate and cooling rate to 10℃ / min to obtain a three-layer asymmetric alumina ceramic membrane, which is in the form of a flat plate. The thickness of the separation layer is 18μm.

[0066] Example 2

[0067] This embodiment provides a method for preparing a three-layer asymmetric aluminum oxide film, and the preparation method is as follows:

[0068] Take 120g of alumina powder with a particle size of 5μm, add 90ml of deionized water, and stir for 2 minutes. During the stirring process, add 2.4g of dispersant hexadecyltrimethylammonium chloride, 2.4g of adhesive hydroxymethyl cellulose, 1.2g of leveling agent polyacrylic acid, 4.8g of plasticizer polyethylene glycol, 2.4g of defoaming agent isopropyl alcohol, 8.64g of sintering aid kaolin, and 0.96g of fumed silica. Then, transfer the casting liquid to a high-speed beater, set the speed to 8000rpm, stir at high speed for 5 hours, perform ultrasonic treatment for 30 minutes to eliminate foam, and let it stand for 2 hours. Next, evenly apply the release agent paraffin oil to the leveled temperature control plate, set to 30°C. The casting instrument uses a polytetrafluoroethylene flat frame with a PET plastic film underneath, and dry it for 12 hours. The cast membrane was then placed in a muffle furnace and calcined at 1400°C for 3 hours at a heating rate and a cooling rate of 10°C / min to obtain a support layer (single-layer symmetrical ceramic membrane) with a thickness of 1 mm.

[0069] Take 56.8g of alumina powder with a particle size of 1μm, add it to 600ml of deionized water, and stir for 5min. During the stirring process, add 1.12g of dispersant hexadecyltrimethylammonium chloride, 10.46g of nitric acid and 6.67g of leveling agent polyacrylic acid in sequence, ultrasonically treat for 30min to remove foam, and prepare 1μm alumina modification liquid (transition layer modification liquid). Use a pulling instrument to pull and dip the prepared alumina support layer for 30 seconds, and dip it twice. After the dip coating is completed, dry it at room temperature for 12 hours, set the roasting temperature to 1200℃, calcine it at high temperature for 3 hours, and set the heating rate and cooling rate to 10℃ / min to prepare a double-layer asymmetric alumina ceramic membrane. The thickness of the transition layer is 10μm.

[0070] Take 51.12g of alumina powder with a particle size of 400nm, add it to 500ml of deionized water, and stir for 5min. During the stirring process, add 1.12g of dispersant hexadecyltrimethylammonium chloride, 12.5g of nitric acid and 6.67g of leveling agent polyacrylic acid in sequence, ultrasonically treat for 30min to remove foam, and prepare 400nm alumina modification liquid (separation layer modification liquid). The double-layer asymmetric alumina ceramic membrane prepared above is pulled and dipped for 30 seconds using a pulling instrument, and dipped twice. After the dip coating is completed, dry it at room temperature for 12 hours, set the roasting temperature to 1200℃, calcine it at high temperature for 3 hours, and set the heating rate and cooling rate to 10℃ / min to obtain a three-layer asymmetric alumina ceramic membrane in the form of a flat plate. The thickness of the separation layer is 18μm.

[0071] Comparative Example 1

[0072] This comparative example provides a method for preparing a three-layer asymmetric aluminum oxide film, and the preparation method is as follows:

[0073] 120g of 10μm alumina powder was added to 8.64g of kaolin and 0.96g of fumed silica as sintering aids, along with 7.2g of hydroxymethyl cellulose as a binder. A hydraulic press was used to form the alumina solid powder into discs with a diameter of 22mm and a thickness of 2mm. Subsequently, the alumina support layer was prepared after calcination at 1200°C for 4 hours.

[0074] Then, the same method as in Example 1 was used to perform impregnation and pulling on the alumina support layer to prepare a transition layer and a separation layer, and finally a three-layer asymmetric disc-shaped alumina ceramic membrane was obtained.

[0075] The gas flux test device was used to test the above examples and comparative examples. The results showed that the N2 flux of Example 1 was 350,000 GPU, the N2 flux of Example 2 was 160,000 GPU, and the N2 flux of Comparative Example 1 was only 120,000 GPU. Figure 8 As shown, the pure water flux of the alumina ceramic membranes of Examples 1 and 2 of the present invention is higher than that of Comparative Example 1. This demonstrates that the membrane material prepared by the casting method achieves a significant improvement in flux. The 5μm powder used as the support layer substrate in Example 2 has a slightly lower flux than the 10μm powder in Example 1. This is because the pore size of the 5μm powder is smaller, which limits the gas flow, but it is still significantly higher than that of Comparative Example 1.

[0076] Figure 5 The flat alumina ceramic membrane finally obtained in Example 1 and the special-shaped membrane after cutting, the shape of the membrane material can be freely controlled. Figure 6 This is the disc-shaped alumina ceramic membrane finally obtained in Comparative Example 1. The shape of the membrane material is fixedly controlled by the size of the mold. Figure 7 The N2 flux comparison chart of the alumina ceramic membrane of each embodiment and comparative example is shown, and the flux of the support layer, two layers and three layers during the preparation process are tested at the same time. It can be seen that with the growth of the transition layer and the separation layer, the flux of the membrane material is gradually decreasing. This is because the particle gaps in the transition layer and the separation layer are getting smaller and smaller, the gas / liquid channels are reduced, and the transition layer and the separation layer also have a certain thickness, which slows down the time for gas / liquid to pass through the membrane material.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a two-layer asymmetric aluminum oxide membrane. The preparation method is basically the same as that of Example 1, except that the separation layer is prepared directly on the support layer without preparing the transition layer. As a result, the particles in the separation layer are too small and directly penetrate into the support layer, i.e., porosity occurs, and an effective asymmetric structure cannot be formed at this time. The SEM image is shown in FIG. Figure 9 shown.

[0079] Comparative Example 3

[0080] This comparative example provides a method for preparing a three-layer asymmetric aluminum oxide membrane. The preparation method is basically the same as that of Example 1, with the only difference being that no kaolin and fumed silica are added to the membrane casting solution (support layer slurry) when preparing the support layer. As a result, the membrane material breaks during high-temperature sintering. Figure 10 shown.

[0081] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.

Claims

1. An alumina ceramic membrane, characterized in that: The alumina ceramic membrane comprises an alumina support layer, an alumina transition layer and an alumina separation layer which are arranged in sequence; the alumina support layer is prepared by casting a support layer slurry, drying and calcining, and the support layer slurry comprises alumina, a binder, a sintering aid and water; the sintering aid is selected from a combination of one or more of kaolin, fumed silica, titanium dioxide, zirconium oxide and yttrium oxide; the particle sizes of alumina in the alumina support layer, alumina in the alumina transition layer and alumina in the alumina separation layer decrease in sequence.

2. The alumina ceramic membrane according to claim 1, characterized in that: The particle size of alumina in the alumina support layer is 4 to 20 μm; the particle size of alumina in the alumina transition layer is 1 to 3 μm; the particle size of alumina in the alumina separation layer is 200 to 800 nm; and / or the sintering aid is a mixture of kaolin and fumed silica; preferably, in the mixture, the mass ratio of kaolin to fumed silica is 1:8 to 1:10; and / or the alumina support layer is a flat plate-shaped α-Al2O3 porous ceramic support layer; and / or the thickness of the alumina support layer is 0.5 to 2 mm; and / or the thickness of the alumina transition layer is 5 to 25 μm; and / or the thickness of the alumina separation layer is 15 to 25 μm.

3. The alumina ceramic membrane according to claim 1, characterized in that: In parts by weight, the support layer slurry includes 100 to 120 parts of alumina, 2 to 2.5 parts of a binder, 8 to 10 parts of a sintering aid and 75 to 90 parts of water; and / or, the binder is selected from one or a combination of two of hydroxymethyl cellulose and polyvinyl alcohol; and / or, the support layer slurry also includes a dispersant, a leveling agent, a plasticizer, and a defoaming agent.

4. The alumina ceramic membrane according to claim 3, characterized in that: In parts by weight, the support layer slurry includes 100-120 parts of aluminum oxide, 2-2.5 parts of dispersant, 2-2.5 parts of binder, 1-1.25 parts of leveling agent, 4-5 parts of plasticizer, 2-2.5 parts of defoamer, 8-10 parts of sintering aid and 75-90 parts of water; and / or, the dispersant is selected from one or more combinations of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride; and / or, the leveling agent is selected from one or a combination of two of polydimethylsiloxane and polyacrylic acid; and / or, the plasticizer is selected from one or a combination of two of polyethylene glycol and dibutyl phthalate; and / or, the defoamer is one or a combination of two of tributyl phosphate and isopropyl alcohol.

5. A method for preparing the alumina ceramic film according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: 1) casting the support layer slurry, drying and calcining to prepare the alumina support layer; 2) impregnating the alumina support layer with a transition layer modification liquid, drying and calcining to obtain an alumina transition layer, wherein the transition layer modification liquid comprises alumina and water; 3) impregnating the alumina transition layer with a separation layer modification liquid, drying and calcining to obtain the alumina ceramic membrane, wherein the separation layer modification liquid comprises alumina and water.

6. The method for preparing an alumina ceramic film according to claim 5, characterized in that: The film casting is carried out in a polytetrafluoroethylene mold; and / or, in step 1), the drying temperature is 30-40°C; and / or, in step 1), the drying time is 8-12h; and / or, in step 1), the calcination temperature is 1200-1600°C; and / or, in step 1), the calcination time is 1-3h.

7. The method for preparing an alumina ceramic film according to claim 5, characterized in that: The transition layer modification liquid also includes a dispersant, a leveling agent and a pH regulator; preferably, in parts by weight, the transition layer modification liquid includes 50 to 60 parts of aluminum oxide, 1 to 1.2 parts of a dispersant, 6 to 10 parts of a leveling agent, 10 to 12 parts of a pH regulator and 500 to 600 parts of water; and / or the pH regulator is selected from one or both of nitric acid and hydrochloric acid.

8. The method for preparing an alumina ceramic film according to claim 5, characterized in that: The separation layer modification liquid also includes a dispersant, a leveling agent and a pH regulator; preferably, in parts by weight, the separation layer modification liquid includes 50 to 60 parts of aluminum oxide, 1 to 1.2 parts of a dispersant, 6 to 10 parts of a leveling agent, 12 to 14 parts of a pH regulator and 400 to 500 parts of water; and / or the pH regulator is selected from one or both of nitric acid and hydrochloric acid.

9. The method for preparing an alumina ceramic film according to claim 5, characterized in that: The preparation method also includes the steps of mechanically stirring and standing the support layer slurry for degassing before the film casting; and / or, in steps 1), 2) and 3), the calcination adopts programmed temperature increase, and the temperature increase rate is 8-12°C / min; and / or, in step 2), two alumina support layers are superimposed on each other, and the gap between them is sealed before impregnation.

10. Use of the alumina ceramic membrane according to any one of claims 1 to 4 in oil-water separation or industrial wastewater treatment.

Citation Information

Patent Citations

  • Alumina plate ceramic membrane with superhydrophobic surface and preparation method thereof

    CN107352980A

  • Preparation method of high-flux ceramic membrane

    CN116422153A

  • Chemical mechanical polishing composition for metalcircuit comprising aluminium hydroxide

    KR1020070018173A